Modelling, analysis and evaluation of a metric system for the quantification of management competitiveness in a system-of-systems complex human corporation - Ayomoh, Michael (University of Pretoria, 2025)
Dissertation (MEng (Industrial Engineering))--University of Pretoria, 2024.